2006
DOI: 10.17221/3649-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Procedure for Mesophyll Protoplast Culture and Plant Regeneration in Brassica oleracea L. and Brassica napus L.

Abstract: An improved protocol for Brassica protoplast culture and plant regeneration was developed. Isolated protoplasts from four-weeks-old in vitro shoot tip culture of Brassica oleracea var. botrytis cv. Siria F1 and Brassica napus doubled haploid of breeding line OP-1 were cultured at a density of 9.8-11.2 × 10 4 protoplasts/ml in darkness at 25°C in a modified medium containing 2% glucose, 0.25 mg/l 2,4-D, 1 mg/l BAP and 1 mg/l NAA. The first divisions of protoplasts were observed on the third day of culture in B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The timing of the first mitotic division is generally expected between 24 and 48 h of culture (Glimelius 1984 ; Mukhopadhyay et al 1991 ), but a shift of the first mitosis to days 3 or 4 of culture, as observed in our study, was also reported for B. oleracea (Fu et al 1985 ; Robertson and Earle 1986 ; Kaur et al 2006 ). Division frequencies in B. oleracea varied as a consequence of the source of tissue, culture system, culture maintenance, and genotype.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The timing of the first mitotic division is generally expected between 24 and 48 h of culture (Glimelius 1984 ; Mukhopadhyay et al 1991 ), but a shift of the first mitosis to days 3 or 4 of culture, as observed in our study, was also reported for B. oleracea (Fu et al 1985 ; Robertson and Earle 1986 ; Kaur et al 2006 ). Division frequencies in B. oleracea varied as a consequence of the source of tissue, culture system, culture maintenance, and genotype.…”
Section: Discussionsupporting
confidence: 83%
“…The use of some types of tissues (such as roots and cortex) leads to a higher risk of contamination, while others (such as hypocotyls and cotyledons) required the use of large amount of seeds to obtain satisfactory yields, and others (such as suspension cultures) are difficult to maintain for Brassica species (Simmonds et al 1991 ). In B. oleracea , protoplasts have previously been isolated mainly from leaves (Fu et al 1985 ; Robertson and Earle 1986 ; Kaur et al 2006 ) and hypocotyls (Glimelius 1984 ; Mukhopadhyay et al 1991 ; Chen et al 2004 ). In this study, both of these sources, taken from sterile conditions, were utilized and protoplasts were readily isolated for all tested accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Before and after the cold treatment, the uppermost fully developed leaf was harvested from each plant and used to assess proline and dehydrin contents. Protoplast-derived calli were prepared following Kaur et al (2006). When the calli had reached a diameter of 5 -8 mm, they were divided into two groups of 20 calli.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Light-stimulated H + extrusion was also reported by Petzold and Dahse (1988) from leaf discs of Vicia faba L. The H + extrusion may accelerate the browning process. Kaur et al (2006) believed that under illumination, the cultures turn brown, thus affecting the division efficiency of protoplasts of Brassica oleracea L. and Brassica napus L. It is possible that the accelerated browning quickly kills cells of leaf explants of 'Fire Flash' and provides little opportunity for cells to respond to the induction. Although more leaf explants produced callus in the dark culture, the induced calluses still died after culture under lighted conditions.…”
Section: Discussionmentioning
confidence: 99%